(untitled) (Physical Education, Health and Social Sciences, 2025)
This empirical study attempts to examine the perspective of the students of commerce who study at intermediate and graduate levels at college in Hyderabad. The significance of learning in English as a foreign language has been the matter of one of the greatest concerns for the policy makers in the province of Sindh Pakistan. The policies formulated once are rarely revisited for the implementation of productive medium of instructions regardless of the concerns of the students and teachers as key players. In this study attempt, the researcher examines the perspective of different students who received education in English as medium of instructions (EMI) and Urdu as medium of instructions (UMI) separately. The data through semi structured interviews with open ended questions from the selected 13 students revealed the challenges and benefits of learning the subject based knowledge in two different languages as Urdu and English. Many similarities in their opinions were identified. For them, the disciplinary knowledge of English as medium instruction was noticeably less than Urdu as medium of instructions. The study results found that the education in mother tongue at college level is more comprehensive to enhance the performance of students in commerce. A constructive approach to bilingual education must be taken into considerations to redress the challenges for students in commerce at colleges related to the policies of medium of instruction in the education system of Sindh. Moreover, the data based result also displays that the pedagogical success could only be obtainable through the mother tongue in education. This clearly provides the evidence for the native languages as a medium of instructions in colleges.